2017
DOI: 10.2741/s482
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced periodontal regeneration using collagen stem cells or growth factors

Abstract: The regeneration of periodontal tissues still remains a challenge in periodontology. The aim of the present study was to examine the regenerative potential of a) different collagen support versus blank, b) different collagen support +/- a growth factor cocktail (GF) and c) a collagen powder versus collagen powder + periodontal ligament stem cells (PDLSCs) comparatively in a large animal model. The stem cells (SC) were isolated from extracted teeth of 15 adult miniature pigs. A total of 60 class II furcation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The study was performed similarly as previously described by our group [ 22 ]. All surgical interventions were performed under sterile conditions and general anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was performed similarly as previously described by our group [ 22 ]. All surgical interventions were performed under sterile conditions and general anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…For application of the cells, 10 6 PDLSC of the 3rd or 4th passage were combined with a collagen powder (fibrillary collagen type I, III, and V from bovine tissue; MedSkin Solutions, Dr. Suwelack AG, Billerbeck, Germany). In brief, after buffering the acidic pH (pH ~4-5) of the collagen powder to a neutral pH value (pH ~7), PDLSC were transferred to the powder [ 22 ]. After 24 h, prior implantation, a life-death-stain was performed in order to evaluate the survival of the stem cells and to ensure that vial cells were used ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Monsarrat et al [54] reported that most of this preclinical research published until 2013, was performed in the dog model (49% of the studies), with MSCs with an autologous origin (63% vs. 14% allogeneic and 28% xenogeneic) and harvested from intraoral sources (63%). MSCs-based therapies have been tested in different periodontal defect models, such as buccal dehiscence, 2 and 3-wall intrabony, and type II and III furcation lesions, as well as critical size supracrestal periodontal defects [75,94,[109][110][111] .…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…In the last years, the study of the tissue-inductive potential of allogeneic [75,94,111] and xenogeneic MSCs [109,110] has increased. These investigations have reported that the use of cells from other species or other individuals is safe, without eliciting relevant immunogenic reactions after their transplantations [109,111] .…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Evidence indicates that current cause-related periodontal therapy is effective in stopping disease progression and reducing local inflammation, but regeneration of periodontal tissues lost as a consequence of disease still poses a challenge both in terms of predictability and magnitude of effect 5 . Several studies 2 , 17 , 24 have evaluated the potential of a host of biological and chemical mediators, particularly growth and differentiation factors, to improve the results of regenerative therapy. Acid root conditioning is one of the first therapeutic approaches developed with this intent 4 , 7 .…”
Section: Introductionmentioning
confidence: 99%